2016
DOI: 10.1558/jircd.v7i1.27932
|View full text |Cite
|
Sign up to set email alerts
|

Speech naturalness ratings and perceptual correlates of highly natural and unnatural speech in hypokinetic dysarthria secondary to Parkinson's disease

Abstract: Despite the importance of speech naturalness to treatment outcomes, little research has been done on what constitutes speech naturalness and how to best maximize naturalness in relationship to other treatment goals like intelligibility. This study investigated the speech naturalness ratings of individuals with dysarthria and the associated perceptual correlates of highly natural and unnatural speech. Four speakers with hypokinetic dysarthria secondary to Parkinson’s disease were recorded and rated for naturaln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…We hypothesized that sentence-level variations in f0 would reduce intelligibility while simultaneously enhancing naturalness (Klopfenstein, 2016). In line with this hypothesis, we found that synthetic speech produced at a fixed f0 level was more intelligible than when produced with sentence-level variation in f0.…”
Section: Intelligibilitysupporting
confidence: 56%
See 1 more Smart Citation
“…We hypothesized that sentence-level variations in f0 would reduce intelligibility while simultaneously enhancing naturalness (Klopfenstein, 2016). In line with this hypothesis, we found that synthetic speech produced at a fixed f0 level was more intelligible than when produced with sentence-level variation in f0.…”
Section: Intelligibilitysupporting
confidence: 56%
“…Klopfenstein (2016) describes an ongoing struggle with balancing naturalness and intelligibility: Naturalness is linked to social communication, whereas intelligibility is often linked to efficacious communication (Anand & Stepp, 2015;Klopfenstein, 2016;Yorkston et al, 2010). An increase in one measure may be accompanied by a decrease in the other, and vice versa (Nusbaum, Francis, & Henly, 1997).…”
Section: Intelligibility and Naturalness Trade-offsmentioning
confidence: 99%
“…This hypokinetic dysarthria affects all motoric subsystems of speech and leads to a reduced modulation of intensity and pitch, slower speech rate, imprecise articulation as well as an overall reduced articulation space [ 3 , 4 ]. Most studies on hypokinetic dysarthria are either based on perceptual intelligibility/ naturalness ratings [ 5 , 6 , 7 , 8 ] or acoustic speech analyses of standardized tasks, such as sustained vowel phonation, oral diadochokinesia (DDK) or a reading text [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to control for prosodic patterns that have been shown to influence the syllable internal coordination patterns, the study uses mini dialogues and avoids standardized tasks. Prosody is an important domain of speech production as it makes communication vivid, emotional, intelligible and more natural [ 5 , 19 ]. The ability to mark prominence (highlighting important words in a sentence) in the different domains of speech production (intensity, durational properties, pitch and vowel production) is tested in two conditions to examine the influence of motor performance on speech production further: without dopaminergic medication (bad motor performance) and with dopaminergic medication (improved motor performance due to levodopa intake).…”
Section: Introductionmentioning
confidence: 99%